Poplavljen arhiv Mestne občine Ptuj ob naravni ujmi julija 2019 ali Kako smo uspešno rešili pisno kulturno dediščino mesta Ptuj iz 90. let 20. stoletja - Zupanič, Katja (Moderna arhivistika, 2022)
It is a fact that floods are one of the many natural disasters, which cause damage in the area of the Ptuj Municipality. They belong to severe natural disasters, which are also the most common ones. In July of 2019, the Ptuj area was hit by a great storm with downpours of rain, which caused floods in the centre of the city. Water flooded also the basement of the City Muncipality. Archival employees determined that the most precious archival records were damaged – minutes of the city council meetings and other important records from the beginning of the 1990s. Measures for their rescue were immediately undertaken. The author presents a best practice example of successful cooperation between the archives and the creator and the rescue mission to preserve the written cultural heritage of the city of Ptuj.
Keywords: flood; freezing documents; izredne razmere; poplava; rescuing written cultural heritage; reševanje pisne kulturne dediščine; state of emergency; zamrzovanje gradiva